Potential Cost Savings Associated with Targeted Substitution of Current Guideline-Concordant Inpatient Agents with Omadacycline for the Treatment of Adult Hospitalized Patients with Community-Acquired Bacterial Pneumonia at High Risk for Clostridioides difficile Infections: Results of Healthcare-Decision Analytic Model from the United States Hospital Perspective - Thomas Lodise; Mauricio Rodriguez; Surya Chitra; Kelly Wright; Nimish Patel (MDPI AG, 2021)
Introduction: Approximately 3% of hospitalized patients with community-acquired bacterial pneumonia (CABP) develop healthcare-associated Clostridioides difficile infection (HCA-CDI). The validated Davis risk score (DRS) indicates that patients with a DRS ≥ 6 are at an increased risk of 30-day HCA-CDI. In the phase 3 OPTIC CABP study, 14% of CABP patients with DRS ≥ 6 who received moxifloxacin developed CDI vs. 0% for omadacycline. This study assessed the potential economic impact of substituting current guideline-concordant CABP inpatient treatments with omadacycline in hospitalized CABP patients with a DRS ≥ 6 across US hospitals. Methods: A deterministic healthcare-decision analytic model was developed. The model population was hospitalized adult CABP patients with a DRS ≥ 6 across US hospitals (100,000 patients). In the guideline-concordant arm, 14% of CABP patients with DRS ≥ 6 were assumed to develop an HCA-CDI, each costing USD 20,100. In the omadacycline arm, 5 days of therapy was calculated for the entire model population. Results: The use of omadacycline in place of guideline-concordant CABP inpatient treatments for CABP patients with DRS ≥ 6 was estimated to result in cost savings of USD 55.4 million annually across US hospitals. Conclusion: The findings of this simulated model suggest that prioritizing the use of omadacycline over current CABP treatments in hospitalized CABP with a DRS ≥ 6 may potentially reduce attributable HCA-CDI costs. The findings are not unique to omadacycline and could be applied to any antibiotic that confers a lower risk of HCA-CDI relative to current CABP inpatient treatments.